Mediating Effect of Digital Readiness on the Relationship between Online Peer Collaboration, Psychological Motivation and Online Engagement in Malaysian Online Distance Learning Higher Institutions - Zahir Osman,; Liana Mohamad,; Ratna Khuzaimah Mohamad, (ASEAN Journal of Open and Distance Learning, 2021)
This study consolidates online peer collaboration, psychological motivation, digital readiness, and online engagement to examine the influence of digital readiness as a mediator in the relationship between online peer collaboration and psychological motivation and online engagement among online distance learning students in Malaysian higher education institutions. For research hypotheses testing, an online survey involving students from different online distance learning higher education institutions in Malaysia was administered, yielding 307 clean data that was used in data analysis. This study adopted the Structural Equation Modeling for data analysis. The statistical software SPSS ver. 23 and SmartPls ver. 3.0 were used. Results revealed that online peer collaboration and digital readiness have a positive and significant direct relationship with online engagement. Digital readiness was a significant mediator in the relationship between online peer collaboration and psychological motivation and online engagement of online distance learning students in Malaysian higher education institutions. This study also revealed the important role of digital readiness in ensuring the effectiveness of online engagement in the online distance learning environment. This study has made a significant contribution to online distance learning higher institutions, lecturers, and students in examining the effectiveness of engagement among online students. (Abstract by authors)